PD‐L1 detection in histology specimens and matched pleural fluid cell blocks of patients with NSCLC. Issue 12 (17th June 2019) - Grosu, Horiana B.; Arriola, Aileen; Stewart, John; Ma, Junsheng; Bassett, Roland; Hernandez, Mike; Ost, David; Roy‐Chowdhuri, Sinchita
ABSTRACT: Background and objective: Analysis of programmed death ligand‐1 (PD‐L1) in tumour samples is necessary to identify candidates for anti‐PD‐L1/PD‐L1 therapy. Because PD‐L1 is evaluated by immunohistochemistry (IHC), an adequate amount of tumour tissue is a prerequisite for PD‐L1 testing. To examine whether pleural fluid might be an alternative to biopsy/resection specimens for IHC evaluation of PD‐L1 in patients with non‐small cell lung carcinoma (NSCLC), we compared PD‐L1 by IHC between histological specimens and matched pleural fluid. Methods: A retrospective cohort study of patients with NSCLC who underwent core biopsy of a lung mass/surgical resection with PD‐L1 IHC and had a pleural fluid cell block (CB) available for PD‐L1 staining was conducted. PD‐L1 was categorized as negative (PD‐L1 in <1% of tumour cells), moderately positive (PD‐L1 in ≥1% to <50%), strongly positive (PD‐L1 ≥ 50) or inadequate for PD‐L1 testing (<100 tumour cells in the CB). Weighted Cohen's kappa was calculated to evaluate the agreement between PD‐L1 on biopsy/resection specimen and pleural fluid for variables with more than two categories. Results: Of the 115 patients included in this study, 82 (71.3%) had at least 100 tumour cells and were included in the analysis. Of these, 80 (97.6%) had adenocarcinoma. For PD‐L1 of histological specimens versus pleural fluid categorized as negative, moderately positive or strongly positive, the weighted kappa statistic was 0.76 (95% CI: 0.64–0.88), and the concordance was 0.78 (95% CI: 0.68–0.86). Conclusion: Correlation and concordance are high between PD‐L1 in histological specimens and matched pleural fluid. Evaluation of PD‐L1 in pleural fluid should be considered in patients unable to undergo histological biopsies. Abstract : Programmed death ligand‐1 (PD‐L1) expression in pleural fluid is reliable with fairly good correlation and concordance with PD‐L1 expression in surgical biopsy/resection specimens and should be considered in patients who are unable to undergo histological biopsies.